Distribution of interleukin-10 family cytokines in serum and synovial fluid of patients with inflammatory arthritis reveals different contribution to systemic and joint inflammation. (2nd January 2015) - Scrivo, R; Conigliaro, P; Riccieri, V; Di Franco, M; Alessandri, C; Spadaro, A; Perricone, R; Valesini, G
Summary: Evidence exists that interleukin (IL)-10 family cytokines may be involved in the pathogenesis of rheumatoid arthritis (RA). We sought to determine whether or not these cytokines are involved in psoriatic arthritis (PsA). We conducted a prospective study on patients with PsA, RA and osteoarthritis (OA); healthy controls (HC) were also included. We analysed IL-20, IL-24 and IL-19 serum and synovial fluid (SF) levels and change of serum levels following treatment with biological agents. IL-20 serum levels were increased in PsA and RA compared with OA patients and HC and with matched SF levels. IL-24 serum levels in PsA, RA and OA patients were higher than those in HC and also with respect to matched SF in PsA. IL-19 serum levels were higher in HC and OA compared with PsA and RA patients; IL-19 SF levels were higher in PsA and RA compared with OA patients, and in PsA compared with RA patients. PsA and RA patients showed a reduction of IL-19 serum levels after biological treatment. Therefore, IL-19 seems to be involved mainly in the joint inflammation, whereas IL-20 and IL-24 appear to participate mainly in the systemic responses. These findings may further the comprehension of the contribution of these cytokines to the inflammatory response involved in chronic arthritis, as well as to the development of novel therapeutic strategies.